2014
DOI: 10.1016/j.envres.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of airborne virus contamination in wastewater treatment plants

Abstract: Concentrations of potentially pathogenic viral particles in WWTP air are non-negligible and could partly explain the work-related gastrointestinal symptoms often reported in employees in this sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 49 publications
2
67
2
4
Order By: Relevance
“…While other studies have reported concentrations of airborne bacteria around WWTPs, 24,27,30,32 fewer have focused on airborne viruses. 34,40 Our results show that viable virus can be aerosolized from an aeration basin. By reporting results not just as concentrations but also as emission rates, they can be extended to other scenarios.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…While other studies have reported concentrations of airborne bacteria around WWTPs, 24,27,30,32 fewer have focused on airborne viruses. 34,40 Our results show that viable virus can be aerosolized from an aeration basin. By reporting results not just as concentrations but also as emission rates, they can be extended to other scenarios.…”
Section: Discussionmentioning
confidence: 74%
“…33 Another study characterized bioaerosols generated in sewage systems indirectly by measuring endotoxin concentrations; endotoxins are a cell wall component of Gram-negative bacteria. 34,35 Up to 80 ng m -3 of endotoxin were detected in the air samples. To our knowledge, there are no studies on aerosolization of viruses in sewers.…”
Section: Potential For Aerosol Transmission Via Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of this route of transmission, surprisingly few studies have examined the potential exposure of WTC workers to pathogenic viruses through the air. Moreover, in these studies, only one or two viruses were analyzed (Romano et al, 1999;Uhrbrand et al, 2011;Masclaux et al, 2014). In Denmark WTCs, noroviruses (Noro) GI and GII were detected for the first time in air samples using personal samplers (Uhrbrand et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…, ; Masclaux et al . ). However, more data regarding which type of filter‐based sampler and filter material that result in the best collection and recovery of NoV is warranted.…”
Section: Introductionmentioning
confidence: 97%